Medical conditions at enrollment do not impact efficacy and safety of the adjuvanted recombinant zoster vaccine: a pooled post-hoc analysis of two parallel randomized trials. Issue 12 (2nd December 2019) - Oostvogels, Lidia; Heineman, Thomas C.; Johnson, Robert W.; Levin, Myron J.; McElhaney, Janet E.; Van den Steen, Peter; Zahaf, Toufik; Dagnew, Alemnew F.; Chlibek, Roman; Diez-Domingo, Javier; Gorfinkel, Iris S.; Hervé, Caroline; et al.
ABSTRACT: In two pivotal efficacy studies (ZOE-50; ZOE-70), the adjuvanted recombinant zoster vaccine (RZV) demonstrated >90% efficacy against herpes zoster (HZ). Adults aged ≥50 or ≥70 years (ZOE-50 [NCT01165177]; ZOE-70 [NCT01165229]) were randomized to receive 2 doses of RZV or placebo 2 months apart. Vaccine efficacy and safety were evaluated post-hoc in the pooled (ZOE-50/70) population according to the number and type of selected medical conditions present at enrollment. At enrollment, 82.3% of RZV and 82.7% of placebo recipients reported ≥1 of the 15 selected medical conditions. Efficacy against HZ ranged from 84.5% (95% Confidence Interval [CI]: 46.4–97.1) in participants with respiratory disorders to 97.0% (95%CI: 82.3–99.9) in those with coronary heart disease. Moreover, efficacy remained >90% irrespective of the number of selected medical conditions reported by a participant. As indicated by the similarity of the point estimates, this post-hoc analysis suggests that RZV efficacy remains high in all selected medical conditions, as well as with increasing number of medical conditions. No safety concern was identified by the type or number of medical conditions present at enrollment. PLAIN LANGUAGE SUMMARY: What is the context? Shingles, or herpes zoster (HZ), is a clinical reactivation of the varicella-zoster virus, which causes chickenpox. HZ refers to the resulting skin rash, which is often accompanied by severe, burning or itching, pain. While HZ generally affects adults over 50 years of age, it is also common in people with weakened immune systems, for example patients undergoing chemotherapy, or those with an underlying medical condition such as diabetes, asthma, or other diseases. What is new? Clinical trials have demonstrated that the risk of experiencing HZ in adults over 50 years of age is substantially decreased after administration of the adjuvanted recombinant zoster vaccine (RZV, Shingrix ). Additional analyses were performed to determine the impact of common medical conditions on the efficacy and safety of Shingrix . These show that underlying medical conditions were common among the trial participants, but Shingrix was still protective against HZ despite their presence. A similar safety profile was reported by participants receiving either placebo or RZV. What is the impact? Shingrix is effective in the prevention of HZ in adults over 50 years of age, including those with one or more of the common medical conditions considered. Results may help inform the use of Shingrix in these individuals.